THE USE OF CODE-SWITCHING AND CODE-MIXING IN ENGLISH LANGUAGE TEACHING AT STATE POLYTECHNIC OF SRIWIJAYA - Muhammad Nadjmuddin (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2012)
This article discusses the usage of Bahasa Indonesia (BI) in EFL classrooms of StatePolytechnic of Sriwijaya (Polsri). The first objective of this study was to examine the language use in theclassroom instruction, in particular, the use code-switching (CS) and code-mixing (CM) and linguisticfactors of the utterances as well as the functions of using CS and CM by the lecturers. Another purposewas investigating the subjects’ perception on the use of CS and CM. This case study collected data fromfour lecturers and their students in English Department, Polsri. The analysis of the classroom corpusidentified seven communication functions in the lecturers’ speeches. The findings of this study alsorevealed that there were different levels of agreement and disagreement on whether a lecturer should useof CS and CM in the EFL classes. Based on the data collected from the subjects’ responses to thequestionnaire, this study concluded that CS and CM were aimed at increasing the efficiency ofinformation conveyed. CS and CM are necessary communicative strategies for lecturers to achieveteaching goals, in particular, involving the students who lack English proficiency.